The Effect of Storytelling Method on Pain Reduction in Children with Acute Lymphoblastic Leukemia (ALL) - Husnanisa Kusuma Wardani; Noor Yunida Triana (LPPM Universitas Harapan Bangsa, 2024)
Acute Lymphoblastic Leukemia (ALL) is the most common type of blood and bone marrow cancer in children. The most important and frequently encountered impact of ALL on children is pain. Pain in children can be treated with non-pharmacological therapy, namely storytelling therapy. Children can distract (distract) their feelings of pain and relax during treatment at the hospital because they feel happy and comfortable when listening to stories. The aim of this case study aims to determine the effect of the storytelling method on reducing pain in children with Acute Lymphoblastic Leukemia (ALL) in the Wijaya Kusuma Chemotherapy Room, Margono Soekarjo Hospital, Purwokerto. This case study design uses a descriptive design with a shelter housing approach. The subject of this case study was 1 respondent who met the inclusion and exclusion criteria, using purposive sampling. Data were collected using fairy tale script instruments and a numerical rating scale. The results of the case study showed a decrease in the pain scale after storytelling therapy was carried out for 3 meetings, resulting in results from scale 6 (Moderate Pain) to scale 2 (Mild Pain). So it can be concluded that the storytelling method can be recommended for children suffering from ALL because it is effective in reducing the pain scale.